Analisis Strategi Pemasaran Dalam Meningkatkan Volume Penjualan Minyak Harum Maluku 52 Pada CV. Alfa Blessing - Novita Noya; Martha Turukay; Paulus M Puttileihalat (CV. Publikasi Indonesia, 2022)
This study aims to find out and analyze how the marketing strategy is used on CV Alfa blessing in increasing sales. This study using qualitative descriptive research methods also uses SWOT analysis (Strength, Weakness, Opportunity, Threat) The results of the study show the value of the total score IFE 3.033 identify that it is used on the Alfà Blessing CV in increasing sales. This study uses the marketing of the fragrant oil of Maluku 52 has a strong internal position, the value of the total score of EFE 2.99 identifies has a strong external potential so that CV Alfa blessing can respond both opportunities and existing threats. The strategic alternatives for marketing Maluku fragrant oil at CV Alfa Blessing are 1) Maintaining and improving product quality, 2) Utilizing the availability of social media to disseminate product information so that it can be recognized by the public, 3) Utilizing government policies to take part in providing management training to human resources to better control the broad market to increas sales, 4) Creating Maluku 52 fragrant oil products that are unique in their benefits to avoid competition, and 5) Conducting socialization with the community.